Characteristics of Adult Intussusception due to Malignancy in Japanese Patients - Shogo Kitahata; Ayaka Nakamura; Yuka Kimura; Mai Fukumoto; Kana Matsuoka; Takuya Matsuda; Kazuya Murakawa; Taisei Murakami; Kei Onishi; Hirofumi Izumoto; Kozue Kanemitsu‐Okada; Tomoe Kawamura; et al. (JGH Open)
ABSTRACT Aims Adult intussusception (AI) is often associated with organic diseases. However, few studies have examined the causes of AI in Japanese patients. This study aimed to elucidate the clinical characteristics of AI due to malignancy in Japanese patients. Methods and Results From 2013 to 2021, 54 Japanese patients with AI (≥ 20 years) diagnosed at our hospital were enrolled and divided into two groups according to the cause of AI (malignancy group, n = 26; other diseases group, n = 28). The patients' clinical characteristics were retrospectively evaluated. Patients in the malignancy group were significantly older than those in the other diseases group (p < 0.001). The cutoff value for age as a factor associated with AI due to malignancy was 64 years (area under the curve: 0.78, 95% confidence interval [CI]: 0.65–0.90). The frequency of chronic symptoms (> 14 days) in AI due to malignancy was significantly higher than the frequencies of acute (≤ 4 days) and subacute (4–14 days) symptoms (p = 0.010 and p = 0.027, respectively). The colonic type of AI was significantly more common than the small intestinal and ileocecal types in the malignancy group (both p < 0.001). Multivariate analysis showed that age of ≥ 64 years, chronic symptoms, and the colonic type were independently associated with AI due to malignancy (adjusted odds ratio [OR] 16.00, 95% CI 1.23–208.00; adjusted OR 32.70, 95% CI 1.50–712.00; adjusted OR 31.20, 95% CI 2.68–363.00, respectively). Conclusion Advanced age (≥ 64 years), chronic symptoms, and AI in the colon are characteristics of AI due to malignancy.